2021
DOI: 10.1021/acs.jcim.1c00879
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into the Human Mitochondrial Pyruvate Carrier Complexes

Abstract: Pyruvate metabolism requires the mitochondrial pyruvate carrier (MPC) proteins to transport pyruvate from the intermembrane space through the inner mitochondrial membrane to the mitochondrial matrix. The lack of the atomic structures of MPC hampers the understanding of the functional states of MPC and molecular interactions with the substrate or inhibitor. Here, we develop the de novo models of human MPC complexes and characterize the conformational dynamics of the MPC heterodimer formed by MPC1 and MPC2 (MPC1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…Mitochondrial uptake is a prerequisite of a subsequent mitochondrial metabolism of pyruvate. To test whether the mitochondrial pyruvate carrier (MPC) is involved in the observed astrocytic pyruvate consumption, we applied UK5099, an inhibitor of the mitochondrial pyruvate carrier [ 23 , 46 , 47 ]. The presence of UK5099 lowered the astrocytic pyruvate consumption in a concentration-dependent manner and completely prevented pyruvate consumption in a concentration of 100 µM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondrial uptake is a prerequisite of a subsequent mitochondrial metabolism of pyruvate. To test whether the mitochondrial pyruvate carrier (MPC) is involved in the observed astrocytic pyruvate consumption, we applied UK5099, an inhibitor of the mitochondrial pyruvate carrier [ 23 , 46 , 47 ]. The presence of UK5099 lowered the astrocytic pyruvate consumption in a concentration-dependent manner and completely prevented pyruvate consumption in a concentration of 100 µM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The dimer was constructed in the inward facing position based on structural alignment with the SemiSWEET transporter X-ray structure (PDB: 4X5M) as a template [ 16 ] ( Figure 2 A,B). During our work on this manuscript, Xu, et al, published a homology model of the MPC dimer and a molecular dynamics simulations study on the model [ 27 ]. Comparison of our homology model with the published model revealed high similarity.…”
Section: Resultsmentioning
confidence: 99%
“…However, because of the lack of sufficient membrane protein structures, the prediction accuracy on membrane proteins is low. Recent literature using RoseTTAFold to calculate the 3D structure of MPCs also showed a different secondary structure from the NMR results [ 13 ]. Though both programs gave the prediction of the tertiary structure of the MPC complex, the differences of the secondary structures between the predictions and experimental results implicate that further structural characterization of the MPC complex is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier study suggested that MPC1 displays two transmembrane segments with the N- and C-termini projecting into the mitochondrial matrix, whereas MPC2 in mammals and MPC3 in yeast probably consist of three transmembrane helices, with the N-terminus projecting in the matrix and the C-terminus in the intermembrane space [ 12 ]. It was recently predicted by AlphaFold2 and RoseTTAFold that MPC1 and MPC2 both display three transmembrane helices [ 13 ]. So far, the membrane topology of MPC1 and MPC2 is still not fully resolved, as no experimental investigations on the structure of MPCs have been reported.…”
Section: Introductionmentioning
confidence: 99%